Chromatin-Based Regulation of Plant Root Development - Chen, Dong-Hong; Huang, Yong; Jiang, Changhua; Si, Jin-Ping (Frontiers in Plant Science, 2018)
Plant is endowed with sessile habit and nutrient acquisition mainly through the root organ, which also provides an excellent model to study stem cell fate and asymmetric division due to well-organized cell layers and relatively simple cell types in root meristem. Besides genetic material DNA wrapped around histone octamer, chromatin structure determined by chromatin modification including DNA methylation, histone modification and chromatin remodeling also contributes greatly to the regulation of gene expression. In this review, we summarize the current progresses on the molecular mechanisms of chromatin modification in regulating root development.